Analysis of Back Pain Risk Factors Among Medical Students: A Cross-Sectional Study - Renata Jabłońska; Karolina Stodolna; Paweł Sokal; Agnieszka Królikowska; Karolina Filipska-Blejder; Beata Haor; Robert Ślusarz (Advances in Public Health)
Conclusion: A high incidence of back pain among students of medical faculty was found, as well as several risk factors—age, gender, field of study, additional work, motherhood/fatherhood, sleep problems. Medical schools should develop and implement appropriate strategies to mitigate modifiable risk factors for back pain among students.